A product-based non-conformance classification - Jamaludin, Roslan (2008)
The research reported in this paper focuses on classihing non-conformances to facilitate the preproduction team in product validation of consumer electronic products. Development of the classification is based on the manifestation of mistakes which results in non-conformances and their relationship with the characterislics of products under validation.A new non-conformance classijication has been defined based on two interconnected aspects: manifestation of mistakes and product characteristics. The research contributes to the understanding of product quality deficiencies as a consequence of mistakes and shows how quality deficiency can be minimised by addressing non-conformances during product validation.